Educational Interventions for Haemodialysis Patients in the Transplant Process: A Systematic Review - Ester Oriol‐Vila; Laura Rota‐Musoll; Esmeralda Molina‐Robles; Carme Roure‐Pujol; Emilia Chiverches‐Pérez (Nursing Open)
ABSTRACT Aim To systematically evaluate empirical studies investigating nursing educational interventions for patients with haemodialysis at the different stages of cadaveric kidney transplantation and synthesise these findings. Design A systematic review of clinical interventions. Methods On clinical trials published in Spanish and English, between January 2005 and July 2022, in the main databases. The number of studies identified is shown in the flowchart of the PRISMA review. For the critical assessment of the scientific quality of the studies, the CASPe checklist and the Cochrane risk of bias assessment tool were applied. Results Eleven studies were obtained in which nursing educational interventions focused on posttransplantations and one that considered care from the person's admission to hospital were evaluated. The results obtained identified four themes: health education, empowerment, quality of life and holistic patient care with the help of different support methods, including individual and personalised support, group format and informational support via an educational brochure, telephone and website. Conclusion The reviewed studies suggest that after receiving educational interventions patient dialysis treatment and kidney transplant recipient, have better health outcomes. Patient Contribution Larger studies are needed to promote a comprehensive and continuous self‐care model throughout the kidney transplant process. Implications for Nursing Health Education Nursing educational interventions are necessary throughout the transplantation process for the patient dialysis and the family in a comprehensive and continuous manner. In the future, clinical trial studies are needed at the pretransplantation stage.